Tropical Cyclone Dynamics, Prediction, and Detection Recent Developments in - Lupo, Anthony R. (IntechOpen, 2016)
Today, tropical cyclones continue to bring destruction, as well as disruption, to societies that are exposed to their threat. This book represents a compilation of recent cutting-edge research on tropical cyclones and their impacts from researchers at many institutions around the world. This book contains new looks at tropical cyclone dynamics, the use of satellite-based remote sensing in the detection and climatology of tropical cyclones, and the modeling and prediction of tropical cyclones as well as their associated impacts. This book would make a nice addition to any course on tropical meteorology highlighting topics of interest in recent research on this topic.